Citric Acid Cycle: Gene-Enzyme Relationships in Bacillus subtilis - Rutberg, Blanka (1970)
The genetic location of mutations affecting the citric acid cycle and the properties of mutants of Bacillus subtilis possessing these mutations have been examined. Genes coding for the component enzymes of the cycle were found to be unlinked to each other and thus do not form an operon. The mutational defect in a mutant lacking fumarase mapped between thr-5 and cysB3. Mutations causing inability to produce isocitrate dehydrogenase and succinate dehydrogenase were found to map between argA11 and leu-1. The α-ketoglutarate dehydrogenase mutations were mapped at the terminal end of the B. subtilis chromosome through a weak linkage in phage PBS-1 transduction of one class of these mutations of ilvA2 and metB4. A second class of α-ketoglutarate dehydrogenase mutations mapped closer to ilvA2 and metB4 but still terminal with respect to these markers. Aconitaseless mutants possessed mutations that could not be linked to any of the known transducing segments of the chromosome. An effect of mutation conferring loss of one enzyme of the cycle on the specific activity of the other enzymes in the cycle was observed.